Impact of SARS-Cov2 pandemic on menstrual cycle in young women - Todic, Ivana (Medicinski podmladak, 2022)
Introduction: Normal and regular menstrual cycle is an important physiological function, that indicates valuable information about women reproductive health, but also overall health. A lifestyle pattern could have influence on hormone activity and potential impact on menstrual regularity. Menstrual abnormalities are very common among adolescent. The aim of this study was to explore if the change of everyday habits, during pandemic, had an influence on hormone activity  and  menstrual regularity among  young women.Material and methods: This study included 169 girls, from 15 to 25 years old, that were doing questionnarie based on menstruation characteristic and daily habits in period from December 2019 to October 2020. Average duration of menstrual cycle, before and during SARS-Cov2 pandemic were analysed.Results: Family members who at some point during pandemic tested positive are present among 29% of respodents. Average time of menarcha was age 12 and 17.6% of them had irregular menstrual cycle. Change of dietry habits was reported by 30% of girls and sleep habit by 35.5%. Also 44% of them had less activites for school and 77% girls spent more time on their mobile phones.Conclusion: : Analysing data from menstraul history of examined girls, we have noticed that there was not  statistically significant difference in menstrual cycle last during pandemic, comparing it to previous period, despite the change of daily habits.
Keywords: menstrual cycle, young women, COVID-19, menstraul abnormalites